Customer Experience Analysis for Students Visiting Cafes in Padang City - Pipi Agustina; Waryono (Journal of Multidimensional Management, 2025)
Cafes have become one of the favorite places for students in Padang. Nowadays, cafes are not just places to eat and drink but have developed into multifunctional spaces. For students, cafes become places to study, discuss, relax, and express themselves. This study aims to analyze the experience of student customers in cafes based on five customer experiences indicators: Sense, Feel, Think, Act, and Related Experience. The method used is qualitative with a phenomenological approach with data collection through interviews, observations, and documentation. The analysis technique in this study includes four stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that Sense Experience is influenced by interior design, cleanliness, and the appearance of employees and visitors. Feel Experience is related to comfort, tranquility, and social interactions that create a relaxed atmosphere. Think Experience arises from a different atmosphere, adequate facilities, and a combination of coffee aroma and music that encourages creative ideas. Act Experience supports learning activities, relaxation, and social interaction, while Relate Experience emphasizes social relationships and identity through cafe facilities, menus, and aesthetics. These findings confirm that comprehensive customer experience management can increase satisfaction, loyalty, and memorability experiences for students